The enhanced n-butanol sensing performance of In2O3 loaded NiO cuboid heterostructure - Perrone, Olavo M. [UNESP]; Roveda, Antonio C.; de Moraes, Daniel A.; Volanti, Diogo P. [UNESP] (My University, 2023)
Monitoring volatile organic compounds (VOCs) quickly and on-site is essential for preserving human health. The semiconductor gas sensor has been a promising strategy for detecting VOCs. However, stability, selectivity, and sensitivity are crucial for the practical application of a gas-sensor material. Innovative synthetic methods have been studied to improve the properties of sensor materials, such as better detection and stability and the construction of p-n heterojunction materials. In this work, NiO/In2O3 heterostructure was synthesized by fast microwave-assisted solvothermal (MAS) using nickel foam and indium nitrate and was studied as a gas sensor for detecting several VOCs. NiO/In2O3 has the combined properties of NiO, a p-type material, and of In2O3, an n-type. NiO/In2O3 presented a superior performance for detecting n-butanol at the ideal operating temperature (350 °C), with a fast response (6 s), good selectivity, and stability. The n-Butanol response at 100 ppm was Ra/Rg = 412 ± 16, and a linear detection range from 1 to 200 ppm was achieved. The best sensing response for this material towards n-butanol is attributed to the electron depletion layer caused by NiO/In2O3 junction and more adsorption sites obtained during fast MAS synthesis.
Keywords: Gas sensor; Heterojunction; Microwave synthesis; Nickel foam; NiO/In2O3; Volatile organic compounds